Evaluation of outcomes after EMS-witnessed traumatic out-of-hospital cardiac arrest caused by traffic collisions. (February 2022) - Kitano, Shinnosuke; Fujimoto, Kenji; Suzuki, Kensuke; Harada, Satoshi; Narikawa, Kenji; Yamada, Marina; Nakazawa, Mayumi; Ogawa, Satoo; Yokota, Hiroyuki
Abstract: Aim: The survival rate of patients with traumatic cardiac arrest is 3% or lower. Cardiac arrest witnessed by emergency medical services (EMS) accounts for approximately 16% of prehospital traumatic cardiac arrests, but the prognosis is unknown. We aimed to compare the 1-month survival rate of cardiac arrest witnessed by EMS with that of cardiac arrest witnessed by bystanders and unwitnessed cardiac arrest in traffic trauma victims; further, the time from injury to cardiac arrest was assessed. Methods: This analysis used the Utstein Registry in Japan and included data of 3883 patients with traumatic cardiac arrest caused by traffic collisions registered between 2014 and 2019 in Japan. Results: The 1-month survival rate was 10.9% in the EMS-witnessed cardiac arrest group; this was significantly higher than that in the bystander-witnessed (7.2%) and unwitnessed (5.6%) cardiac arrest groups ( P  < 0.01). The median time from injury to cardiac arrest was 18 min (25% quartile: 12, 75% quartile: 26). Conclusion: The 1-month survival rate was significantly higher in the EMS-witnessed cardiac arrest group than in the bystander-witnessed and unwitnessed cardiac arrest groups. It is important to prevent progression to cardiac arrest in trauma patients with intact respiratory function and pulse rate at the time of contact with EMS. A system for early recognition of severe trauma is needed, and a doctor's car or helicopter can be requested as needed. We believe that early recognition and prompt intervention will improve the prognosis of prehospital traumatic cardiac arrest.